2015
DOI: 10.1136/ebmed-2015-110274
|View full text |Cite
|
Sign up to set email alerts
|

Not a Humbug: the evolution of patient-centred medical decision-making

Abstract: This 'Christmas Issue'-type paper uses the framework of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Some patients might only want basic information when faced with the diagnosis of cancer, whereas others wish for more in-depth information and support during the deliberation process [ 1 , 46 ]. Furthermore, quantitative decision support systems have been described as useful tools that can be helpful for clinicians to offer patients sound information in terms that patients can understand, while engaging them in the decision-making process [ 34 ]. In our study, participants reported that SDM does not take place due to patients not wanting or not being able to decide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients might only want basic information when faced with the diagnosis of cancer, whereas others wish for more in-depth information and support during the deliberation process [ 1 , 46 ]. Furthermore, quantitative decision support systems have been described as useful tools that can be helpful for clinicians to offer patients sound information in terms that patients can understand, while engaging them in the decision-making process [ 34 ]. In our study, participants reported that SDM does not take place due to patients not wanting or not being able to decide.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research on current perceptions on SDM in oncology in Germany is missing. However, to successfully implement SDM in routine cancer care in Germany, it is indispensable to understand the whole process of decision-making from a multidisciplinary perspective [ 26 , 33 , 34 ]. Only if implementation strategies are grounded on the attitudes and experiences of HCPs in a specific setting and health care system, they are likely to be effective [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews are being increasingly employed by health policy-makers, researchers and even patients to assist decision-making processes. [1][2][3][4] Cochrane is known as an independent non-for-profit organization that plays a crucial mediating role in creating, evaluating and disseminating reliable, invaluable and practical information in the format of systematic reviews and metaanalyses. With its well-deserved reputation, Cochrane has facilitated the use of applied research for practical purposes for more than two decades, including prevention, treatment and diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, though research has shown that finances lead many patients to stop treatment, no studies have explored how patients actually view and make these decisions, and are affected by these stresses. Needs exist for evidence-based medicine informed by patient values; but various challenges may arise [ 20 ]. Rational decision making models, drawing on multiple criteria, have been applied regarding use of technology in many domains, such as the environment [ 21 ] and various aspects of health care [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Needs exist for evidence-based medicine informed by patient values; but various challenges may arise [ 20 ]. Rational decision making models, drawing on multiple criteria, have been applied regarding use of technology in many domains, such as the environment [ 21 ] and various aspects of health care [ 20 ]. Such modeling has been applied to one aspect of ARTs—hypothetical decisions, using strictly biological criteria, of whether to transfer one or more than one embryo into the uterus [ 22 ].…”
Section: Introductionmentioning
confidence: 99%